THE NEED FOR REVITALIZING ZAKAH REGULATION TOWARD PRODUCTIVE ZAKAH - M. Zidny Nafi' Hasbi (Al ' Adalah)
Zakah management needs to be revitalized as the results achieved are far from the goals set. The efficient collection of zakah will contribute to people's welfare. This study analyzes Yusuf Qaradawi's productive zakah perspective in Fiqh al-Zakah to examine the regulation of management zakah in Indonesia. Adopting Qaradawi's thought, the government should develop the zakahs' rules, management, and implementation. The government also needs to re-regulate zakah from Muslim communities, such as zakah of professions, agriculture, plantations, gold, silver, and the like. Likewise, if the zakah provisions have been reached (nisab and haul), the government must take zakah out from savings or deposits owned by Muslim communities in banks.